LQR CONTROL APPROACH APPLIED TO UNINTERRUPTIBLE POWER SUPPLY (UPS) - admin, RABHI BOUALAGA,; AMMAR, MOUSSI (Courrier du Savoir; Vol. 8 (2007): Courrier du Savoir)
This paper presents a control strategy applied to high power uninterruptible power supplies with a low switching frequency. In the controller design, the gains are determined by minimizing a cost function, which reduces the tracking error and smoothes the control signal. A recursive least square estimator identifies the parameters model at different load conditions. Then the linear quadratic controller gains are adapted periodically. The output voltage is the only state variable measured.The other state variables are obtained by estimation process. Simulation results show that the proposed control strategy offers good performances for either linear and non-linear loads with low total harmonic distortions (THD) even at low frequencies making it very useful for high power applications.